Source Related Argumentation Found in Science Websites: A quantitative study - Barnes, Ralph; Neumann, Zoë; Draznin-Nagy, Samuel (Informal Logic)

(untitled) (Informal Logic, 2020)
In this paper, we consider the way that web documents seeking to persuade readers of certain science claims provide information about the sources of the arguments. Our quantitative analysis reveals that web documents in our sample include hundreds of examples in which the reader is provided information regarding the trustworthiness (or lack thereof) of sources. The web documents also contain a large number of examples in which the reader is provided with information about how many individuals hold a particular belief. We discuss ad hominem, ad verecundiam, and ad populum arguments, and the way that the examples found in our sample of documents are related to these argumentation schemes.